2019
DOI: 10.1177/1534735419828824
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of 5-Fluorouracil-Based Chemotherapy Combined With Traditional Chinese Medicines for Colorectal Cancer Treatment

Abstract: This meta-analysis evaluates the clinical evidence for the addition of traditional Chinese medicines (TCMs) to 5-fluorouracil (5-FU)-based regimens for colorectal cancer (CRC) in terms of tumor response rate (TRR). Five electronic databases were searched for randomized controlled trials of 5-FU-based chemotherapy combined with TCMs compared to the same 5-FU-based regimen. Forty-five randomized controlled trials were involved in this study, and all the data were analyzed by Stata software (version 14.0). Our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…For CRC, 5-Fu and oxaliplatin are the main chemotherapy drugs used by oncologists for the treatment of CRC. [ 25 ] Due to the general toxicity of the drugs, chemotherapy results in some side effects. Some cancer patients cannot adhere to the effective chemotherapy cycle, the side effects of chemotherapy affect the treatment effect and the QOL.…”
Section: Discussionmentioning
confidence: 99%
“…For CRC, 5-Fu and oxaliplatin are the main chemotherapy drugs used by oncologists for the treatment of CRC. [ 25 ] Due to the general toxicity of the drugs, chemotherapy results in some side effects. Some cancer patients cannot adhere to the effective chemotherapy cycle, the side effects of chemotherapy affect the treatment effect and the QOL.…”
Section: Discussionmentioning
confidence: 99%
“…Active compounds of HQ were screened under the criteria of oral bioavailability (OB) ≥30% and drug-likeness (DL) ≥0. 18.…”
Section: Retrieval Of Chemical Ingredientsmentioning
confidence: 99%
“…A series of recent retrospective experimental studies have shown that conventional chemotherapeutics based on FOLFOX 4, 5-FU, and oxaliplatin can be used in combination with HQ and other Chinese herbal medicines to treat mid- to advanced-stage CRC. It can improve the quality of life of patients showing that increases the tumor response rate (TRR) and reduce the incidence of severe neutropenia, nausea, vomiting, and neurotoxicity associated with chemotherapy, showing that HQ has a good antitumor activity in the treatment of CRC ( 9 , 18 , 19 ). Nevertheless, the ingredients and targets of HQ in CRC need to be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…Although the response rate to 5-FU as a single antitumor medicine is typically below 20%, there are interindividual differences regarding the clinical effectiveness of 5-FU-based chemotherapy[ 12 , 13 ]. 5-FU is a synthetic pyrimidine antagonist (uracil analog) and belongs to the group of anticancer medicine known as antimetabolites[ 14 , 15 ].…”
Section: Fluorouracil-based Chemotherapy and Crcmentioning
confidence: 99%